2016
DOI: 10.4103/0976-7800.195692
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of female sexual dysfunction among Indian fertile females

Abstract: Background:Female sexual dysfunction (FSD) is described as difficulty experienced by a female during any stage of a normal sexual activity including physical pleasure, desire, arousal, or orgasm. There are various factors responsible for FSD including psychological status of a person, gynecological or medical problems, long use of certain drugs, and social beliefs.Objectives:To study the prevalence and various factors associated with FSD.Materials and Methods:Study Design - This study design was a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 14 publications
1
28
1
2
Order By: Relevance
“…However, an Indian study conducted in Ahmedabad on young reproductive age females (20–47 years), showed higher prevalence of FSD in females with upper-middle status (36.47%) as compared to lower socioeconomic status (15.29%). [25]…”
Section: Discussionmentioning
confidence: 99%
“…However, an Indian study conducted in Ahmedabad on young reproductive age females (20–47 years), showed higher prevalence of FSD in females with upper-middle status (36.47%) as compared to lower socioeconomic status (15.29%). [25]…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was designed on the basis of prior used ones in various studies but was finally designed in context to our patient scenario. [ 7 8 ] We modified the existing questionnaire according to our local needs. Patients were recruited from the general outpatient department (OPD) of department of obstetrics and gynecology.…”
Section: Ethodologymentioning
confidence: 99%
“…[ 4 ] In a recent study done on 153 females in Ahmedabad between 2105–2016, 55.5% women had one or the other sexual dysfunction. [ 8 ] In a retrospective review by Pal et al . 2017, of the 237 patients attending the sexual clinic, 235 (99.2%) were male and rest were female.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Hypoactive sexual desire disorder and sexual arousal disorder are amongst the most common sexual dysfunction disorders seen in women. [32][33][34][35] DSM-5 has now come up with female sexual interest/ arousal disorder as one entity which has the criteria that there should be absent or reduced interest in sexual activity and thoughts, absent or reduced sexual excitement, and arousal with decreased sensations which have persisted for a period of at least 6 months. Inclusion of both desire (sexual interest) and arousal together brings into focus the difficulty involved in delineation of phases in female sexual response.…”
Section: Female Sexualitymentioning
confidence: 99%